2020
DOI: 10.1186/s12960-020-00494-8
|View full text |Cite
|
Sign up to set email alerts
|

How should community health workers in fragile contexts be supported: qualitative evidence from Sierra Leone, Liberia and Democratic Republic of Congo

Abstract: Background: Community health workers (CHWs) are critical players in fragile settings, where staff shortages are particularly acute, health indicators are poor and progress towards Universal Health Coverage is slow. Like other health workers, CHWs need support to contribute effectively to health programmes and promote health equity. Yet the evidence base of what kind of support works best is weak. We present evidence from three fragile settings-Sierra Leone, Liberia and Democratic Republic of Congo on managing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 28 publications
(34 reference statements)
5
62
0
Order By: Relevance
“…Motivating factors described by the CHWs in our assessment largely overlap with those from previous studies ( 31 35 ). A study carried out in Tanzania found that dedication to public service, desire for health knowledge, personal pride, and positive reception by community members served as sources of CHW motivation ( 32 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Motivating factors described by the CHWs in our assessment largely overlap with those from previous studies ( 31 35 ). A study carried out in Tanzania found that dedication to public service, desire for health knowledge, personal pride, and positive reception by community members served as sources of CHW motivation ( 32 ).…”
Section: Discussionmentioning
confidence: 59%
“…Previous research suggests that CHWs in LMICs tend to be inundated with many tasks ( 22 , 33 , 38 ), which reinforces the results of our assessment. In addition to multiple responsibilities, research from Sierra Leone, Liberia, and the Democratic Republic of Congo suggests that CHWs sometimes take on second jobs because financial incentives they receive are limited, and this may result in CHWs being not fully committed to their healthcare duties ( 31 , 39 ). Unfulfilled stipend disbursements demotivated CHWs in our assessment, which is also a persistent challenge in other settings ( 33 , 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Policy preferences for CHW selection need to reflect community realities. For example, in fragile settings such as in Liberia and the Democratic Republic of the Congo, it was challenging to find candidates who were literate, though the policy included literacy as a requirement [ 83 ]. In Sierra Leone and Liberia, the policies state a preference for female CHWs.…”
Section: Resultsmentioning
confidence: 99%
“…In Sierra Leone and Liberia, the policies state a preference for female CHWs. However, in Sierra Leone there were more male candidates due to hesitancy on the part of women to apply (due to cultural norms), while in the Democratic Republic of the Congo there were more female CHW candidates because of the many active women’s associations there [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…This broad, analytical transactional framework is based on existing models Kok et al, 2015;Palazuelos et al, 2013) and ndings that have been used by others to validate the framework to support improvement of healthcare services through policy development (Dieleman et al, 2011;Kok et al, 2015;. These frameworks can also be employed in fragile and con ict affected contexts, although the evidence base related to their application is weak (Raven et al, 2020a).…”
Section: Community Healthcare Worker Performance Frameworkmentioning
confidence: 99%